Drivers of customer loyalty and word of mouth intentions: moderating role of interactional justice. Issue 8 (17th November 2018) - Saleem, Muhammad Abid; Yaseen, Asif; Wasaya, Allah
ABSTRACT: This paper proposes a conceptual model of the antecedents of customer loyalty and word of mouth (WOM) intentions with the moderating influence of interactional justice. Using data from 500 tourist respondents at six different tourist locations in the districts of the northern province of Pakistan, the study reported here extends the theoretical and empirical body of evidence regarding customers' perceptions of the quality and value of hotel services and their impact on customer loyalty and WOM intentions. The moderating role of interactional justice perceptions is also studied. The results show that service quality and relationship quality are significant predictors of customer loyalty and WOM intentions. Perceived service value also significantly mediated all the conceptualized relationships. Interactional justice moderated the mediated relationships. Surprisingly, the image of hotels appeared insignificant and did not mediate the most of the relationships. The findings demonstrate that hotel marketers should not assume that all customers' perceptions represent similar underlying value in developing loyalty and WOM intentions.